Cardiopulmonary Aerobic Fitness Assessment During Maximal and Submaximal Exercise Testing in Pediatric Oncology Patients After Chemotherapy. (November 2018) - Powell, Adam W.; Nagarajan, Rajaram; Mays, Wayne A.; Chin, Clifford; Knilans, Timothy K.; Knecht, Sandra K.; Amos, Michelle A.; Gerdes, Yvette M.; Ryan, Thomas D.
Abstract : Purpose: The cardiopulmonary exercise test (CPET) is a valuable tool to assess cardiopulmonary exercise capacity in pediatric oncology patients after chemotherapy. In addition, few studies on the utility of submaximal testing have been performed, which could be important as some patients are unable to complete a maximal effort test secondary to deconditioning by both disease and treatment. Materials and Methods: We performed a retrospective chart review of pediatric cancer patients exposed to chemotherapy from 1992 to 2013 who underwent CPET with cycle ergometry (n=27). The study patients were compared with age-matched, sex-matched, and size-matched normal controls. The submaximal measure recorded was the oxygen consumption (VO2 )@respiratory exchange ratio (RER) 1.0 during a maximal effort test. Results: The chemotherapy group demonstrated significantly lower exercise time (9.2±3.6 vs. 11.4±3.8; P =0.008), total work capacity (4914.4±3290.3 vs. 7664.4±4289.5; P =0.004), systolic blood pressure at peak exercise (162.9±23.2 vs. 177.3±23.8; P =0.01), indexed peak VO2 (33.9±6.9 vs. 40.0±6.3; P =0.001), and indexed peak oxygen pulse (6.1±1.3 vs. 7.0±1.5; P =0.004)). For the submaximal outcome measured, 11/27 of the chemotherapy patients had VO2 @RER 1.0 values <−2 SD from the mean compared with 0/27 control patients. Conclusions: Pediatric patients exposed to chemotherapy have impaired cardiopulmonary exercise capacity. The VO2 @RER 1.0 in chemotherapy patients suggests that this may be a reliable submaximal measure in this population. Implications for Cancer Survivors: This study demonstrates that the CPET can be used in pediatric cancer survivors with prior exposure to chemotherapy to demonstrate impaired cardiopulmonary exercise tolerance, which is demonstrated on submaximal and maximal effort testing.